Cryo-electron microscopy studies of empty capsids of human parvovirus B19 complexed with its cellular receptor. - Chipman, P R (1996)
The three-dimensional structures of human parvovirus B19 VP2 capsids, alone and complexed with its cellular receptor, globoside, have been determined to 26 resolution. The B19 capsid structure, reconstructed from cryo-electron micrographs of vitrified specimens, has depressions on the icosahedral 2-fold and 3-fold axes, as well as a canyon-like region around the 5-fold axes. Similar results had previously been found in an 8 angstrom resolution map derived from x-ray diffraction data. Other parvoviral structures have a cylindrical channel along the 5-fold icosahedral axes, whereas density covers the 5-fold axes in B19. The glycolipid receptor molecules bind into the depressions on the 3-fold axes of the B19:globoside complex. A model of the tetrasaccharide component of globoside, organized as a trimeric fiber, fits well into the difference density representing the globoside receptor. Escape mutations to neutralizing antibodies map onto th capsid surface at regions immediately surrounding the globoside attachment sites. The proximity of the antigenic epitopes to the receptor site suggests that neutralization of virus infectivity is caused by preventing attachment of viruses to cells.